Peran Filantropi Islam Wakaf dalam Kebencanaan - Pertaminawati, Hendra (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
This study explores the opportunities and obstacles in utilizing waqf as a component of alternative funding during the disaster cycle. Indonesia faces a significant risk of natural disasters; nonetheless, funding for prevention, readiness, and rebuilding remains insufficient. Conversely, as the nation with the highest Muslim population globally, the significance of Islamic philanthropy, specifically the potential of waqf in Indonesia, is substantial, integrating waqf into disaster management if executed correctly and backed by a sufficient ecosystem, including effective regulations and supportive administration. Indonesia is a nation that frequently faces natural disasters because of its geographically susceptible position, including the equatorial line, the convergence of tectonic plates, and the Circum-Pacific and Circum-Mediterranean zones. Catastrophes result in considerable economic damage, resulting in heightened poverty levels. Waqf can serve as a pertinent funding source for disaster management since its main aim is to use waqf assets based on their purposes, allowing it to effectively act as a tool for disaster prevention and for rebuilding after disasters. Through the use of waqf resources, the government, along with waqf management organizations, can oversee waqf funds as disaster relief funds to assist in managing disasters in Indonesia. The prospect for waqf in Indonesia is shown to be substantial, as illustrated by the waqf land in 2003, which spanned 154 hectares and had an estimated value of IDR 590 trillion. As of March 2024, waqf land is distributed across 440,512 sites, comprising 72% mosques and prayer areas, 14.5% madrasas, 4.5% burial grounds, and 9% various others.